Correlation between Emotional Intelligence and Online Gaming Addiction with Students’ Mathematical Critical Thinking Ability - Septian, Ari; Inayah, Sarah; Adetia, Elsa (PRISMA, 2025)
The purpose of this study was to determine the relationship between emotional intelligence and mathematical critical thinking skills with online game addiction as a control variable. This study uses a quantitative approach with a survey design. This research is research using the partial correlation method. The population in this study were students of SMA Negeri 1 Cianjur. The subjects of this study were students of class XII IPS SMA Negeri 1 Cianjur in the 2022/2023 academic year who demonstrated tendencies of online gaming addiction. The sample in this study was 32 students of class XII-IPS SMA Negeri 1 Cianjur. The sampling technique was carried out by purposive sampling. The research instrument used was a test instrument to measure mathematical critical thinking skills and a questionnaire used to measure emotional intelligence and online game addiction. The data analysis technique used is a statistical test, namely a partial correlation test using the Smart-PLS application. A partial correlation analysis was conducted using Kendall’s Tau coefficient. That is, there is no relationship between emotional intelligence and students' mathematical critical thinking skills with online game addiction as a control variable. The findings of this study imply that emotional intelligence and online gaming tendencies are significant variables that should be taken into account by educators, institutions, and researchers in efforts to enhance students’ mathematical critical thinking ability and to inform subsequent scholarly inquiry.